Sistem Informasi Rekam Medis data Pasien Pada Puskesmas Kedaton Berbasis Web: Haris Saputro (Universitas Mahakarya Asia, 2021)
The Kedaton Public Health Center is a health center located in the Kedaton Peninjauan Raya sub-district, Ogan Komering Ulu district. For health services for all the people of the Kedaton sub-district, the review of the medical record data recording system still uses the manual method recorded in books.The Online-Based Medical Record Information System at the Kedaton Health Center includes the processing of Medical Records, Patient Data, Drug Data, Action Data, Doctor Data, and admin configuration, but the system built does not cover all administration in the Kedaton Public Health Center. In this study, the method used is aimed at analyzing the problems that occur at the Kedaton Public Health Center and designing a Medical Record Information System which will be implemented in the form of an online-based application.The results of the research from the application of the Medical Record Information System at the Kedaton Health Center, refer to the increased performance of the medical team, so that the process of providing health services to the community can be carried out quickly and easily.